Analisis Pertumbuhan Ekonomi dan Ketimpangan Wilayah Dalam Upaya Pencapaian Pembangunan Berkelanjutan di Provinsi Jambi - Taufik Z. Karim; Heeppy Haryadi Harahap; Mardalena Mardalena (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study aims to find regional economic growth in Jambi Province, regional inequality, and sustainable development achievements in Jambi Province. The research method uses quantitative methods. The secondary data used is in the form of time series data for 2010-2021. Data analysis techniques were carried out using the Klassen Typology method, the Williamson inequality index, Theil Entropy Index, and the Promethee method to make decision criteria. The study results show that the economic growth of the districts/cities in Jambi Province included in Quadrant I is the City of Sungai Full. Quadrant II is Tanjung Jabung Timur and Tanjung Jabung Barat. At the same time, Quadrant III is Kerinci Regency, Merangin Regency, Sarolangun Regency, Batanghari Regency, Muaro Jambi Regency, Tebo Regency, Bungo Regency, and Jambi City. In Quadrant IV, no districts/cities fall into this category. The results of the Williamson Index have inequality criteria from low to moderate. The low inequality value is in Batanghari Regency, and the high is in West Tanjung Jabung Regency. While the highest Theil Entropy index value is in West Tanjung Jabung Regency, with a value of 2.84, and the lowest value is in Merangin Regency, with a value of 0.44. Meanwhile, the results of the analysis of sustainable development using the Promethee method show that Sarolangun Regency has the highest score of 0.4750, and the lowest level of achievement of sustainable development is Merangin Regency with a score of -0.4000.